CREATION AND OPERATION OF SERVICE SECTOR QUALIFICATION CENTERS ON THE BASIS OF PUBLIC-PRIVATE PARTNERSHIP (Innovative professional education, 2024)
The significance of establishing qualification centers in the service sector on the basis of public-private partnerships for awarding and verifying professional qualifications is analyzed. The centers improve the quality of vocational training and ensure thatqualifications meet the demands of the modern labor market. Qualification centers are defined as independent institutions that facilitate objective assessment of professional competencies, aligning standards at both national and international levels. The role of state policy in supporting qualification centers through funding, legal regulation, and standardization is highlighted. The importance of the private sector in creating advanced tools and technologies that enhance the efficiency and transparency of the assessment process is demonstrated.
Keywords: qualification center, professional qualification, public-private partnership, independent assessment, qualification awarding